Comparative studies on the stenogamous and eurygamous behavior of eight Anopheles species of the hyrcanus group (Diptera: Culicidae) in Thailand - Adulsak Wijit (2018)
© by the authors; licensee MDPI, Basel, Switzerland. Establishment of laboratory colony is essential for mosquito-borne-disease research. Mating behavior of stenogamous Anopheles peditaeniatus and seven eurygamous species (Anopheles argyropus, Anopheles crawfordi, Anopheles nigerrimus, Anopheles nitidus, Anopheles paraliae (=An. lesteri), Anopheles pursati and Anopheles sinensis), were investigated and compared in this study. The self-mating success of adult mosquitoes in different size cages at two density resting surface (DRS) values, 3.6 and 7.2, was statistically significant between stenogamous and eurygamous species. The results obtained from comparative measurements of specific characters in adult females (maxillary palpomere and antennal sensilla characters) and males (wing and genitalia) indicate those characters might influence the mating success of An. peditaeniatus in a small cage. The gonostylus of An. peditaeniatus was shorter than the eurygamous species. Additionally, the lower frequency of clasper movement and shorter mating time could be important mechanisms that control the stenogamous behavior of An. peditaeniatus. Interestingly, for the first time, a cluster of large sensilla coeloconica was recorded on the antenna of An. argyropus and An. peditaeniatus females. There was no statistically significant difference in the mean number per female of those large antennal sensilla coeloconica among six of the eurygamous species.